FORMULASI VANISHING CREAM MINYAK ATSIRI RIMPANG JAHE (Zingiber officinale Roxb) DAN UJI AKTIVITAS REPELAN TERHADAP NYAMUK Aedes aegypti BETINA - Azis Ikhsanudin (Universitas Ahmad Dahlan, 2012)
The essential oil of Ginger rhizome is a natural subtance which has been provedto have a repellent effect to the mosquito. The aim of this study was to know the effect ofthis subtance/these substances in vanishing cream dosage forms as repellant to thefemale Aedes aegypti mosquito. The essential oil of Ginger rhizome was isolated withaqueous vapor destillation. Then the result was determined for its physical properties,these were: viscosity, adhesivity, spreadibility and its repellant effect to mosquito aswell. The vanishing cream formulation, containing variation of the essential oilconcentration were prepared, these were: FI (formulation I), FII, FIII, FIV and FV,containing 6,25%, 12,5%, 15%, 20% and 25% of the essential oil respectivity. Eachformulas were tested for their physical properties were viscosity, adhesivity,spreadibility and its repellant effect to mosquito as well. The datas were analyzed.Statistically using SPSS version 16 with Kolmogorov-Smirnov and continued with thet-test (Mann-Whitney) (=0,05). The result showed that the duration of the adhesivityof FI was the longest than the others (1,37±0,15 minutes); the spreadibility of the FIwas widest (71,69±1,76 mm2), and the viscosity was the largert than others (27±0 cps).The repellant capasity of the FV was the longest than the others (47,3±1,80 minutes).